2008
DOI: 10.1002/gps.1956
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes and practices of general practitioners regarding dementia diagnosis in Ireland

Abstract: Findings provide compelling evidence that training and access to diagnostic services are only two of several different structural and ideological obstacles that GPs encounter when attempting to diagnose dementia. Future educational supports for GPs need to be developed which concentrate on these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 20 publications
4
127
0
7
Order By: Relevance
“…An Ireland [16] finding was the similar with our result. Also, we found, the general concept of dementia in not positive-it is considered a disease of elderly.…”
Section: Mostly Dementia Patients Visited In Primary Caresupporting
confidence: 92%
See 1 more Smart Citation
“…An Ireland [16] finding was the similar with our result. Also, we found, the general concept of dementia in not positive-it is considered a disease of elderly.…”
Section: Mostly Dementia Patients Visited In Primary Caresupporting
confidence: 92%
“…In next study, only 47.6% of GPs received training in the diagnosis and management of dementia and only 43.9% used specific protocols to diagnosis. As well as rest of them focused some need for more support for families, more respite care, day centres and social activities for people with dementia [16]. A growing number of studies [17] [18].…”
Section: -4 Minute Gpcog (Verbal 4-5) Minute and Minute Screenmentioning
confidence: 99%
“…General practitioners have highlighted their lack of knowledge about community services and resources, about making the diagnosis and the ability to distinguish between dementia and normal ageing (and the subsequent fear of making a false diagnosis), and about how to communicate the diagnosis (216). Other themes which have been identified as potential barriers to diagnosis include perceived lack of available support services, therapeutic nihilism, late presentation (which is sometimes due to mistaking the signs of dementia for normal ageing), practitioners' own emotional responses and stigma (216)(217)(218).…”
Section: Workforce Attitudes and Knowledgementioning
confidence: 99%
“…Some recent studies have specifically highlighted stigma as a factor that may interfere with timely diagnosis (218)(219)(220)(221) and with communicating the diagnosis (175,218,222,223). On the basis of a five-country qualitative study involving multidisciplinary focus groups, the researchers concluded that stigma is the most powerful obstacle to timely diagnosis (220).…”
Section: Workforce Attitudes and Knowledgementioning
confidence: 99%
“…The former includes stigma or delayed presentation (9,10). The practitioner factors include diagnostic uncertainty or perceived lack of knowledge (11,12), therapeutic nihilism (13), and concerns about disclosing the diagnosis (14). These factors are shared by primary care and community nurses (15).…”
Section: Introductionmentioning
confidence: 99%